The opening of the Magellan Strait and its geodynamic implications - Ghiglione, Matias (2013)
The existence of a Neogene-Quaternary rift system responsible for the opening of the eastern Magellan strait has been one of the more peculiar tectonic features of the southernmost Andes since its discovery more than a decade ago. However, until now there has been no explanation pinpointing the specific tectonic factors that led to the development of the rift. This work focuses on the interaction between the fault systems and the tectonic regimes that have affected Tierra del Fuego north of the South America–Scotia left lateral strike-slip plate boundary. Due to a good match between a Jurassic extensional fault array orientation and the principal stress directions related to the strike-slip plate boundary, we conclude that Jurassic transfer faults reactivated extensionally generating the Magellan rift system. This process was enhanced by northward continental drift, and has implications for the geodynamic behind the separation of South America from Antarctica.